The Impact of Product Quality, Price and Distribution on Purchasing Decision on the Astra Motor Products in Jakarta - Sri Wahyuni; Mervianna Ginting (Arthatama, 2017)
Motorcycle competition is growing rapidly, making motorcycle manufacturers in Indonesia compete to increase the sales of each company and achieve sales targets. This relates to company stakeholders, especially to marketing managers so that they can retain both old and new customers. The purpose of this study was to examine the effect of product quality, price, and distribution of purchasing decisions on Honda Vario 125-FI motorcycles at Astra Motor Jakarta. Research respondents were drawn from 110 consumers at Astra Motor Jakarta. Methods of collecting data using a questionnaire with a Likert scale 1-10. The data analysis technique uses the Structural Equation Modeling (SEM) AMOS program version 21.0 to verify the causality of the three research hypotheses. The results of this study indicate that product quality does not have a significant effect on purchasing decisions, and prices have a significant positive influence on purchasing decisions. Meanwhile, distribution does not have a significant positive effect on purchasing decisions.